DIATOMOLOGICAL STUDIES FROM THREE WATER BODIES OF JAIPUR (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
In suspected drowning cases forensic pathologists are often asked whether the drowning  was anti-mortem or post-mortem, and along with this an equally important question to be  answered here is that if the death really took place at the same site from where the body was  recovered. Here question arises about the exact site of drowning and in forensic investigations;  it imparts necessity for the precise localization of site of drowning. The proposed study deals  with the algological analysis that, in turn has recorded diatom type in three water bodies of  Jaipur (Rajasthan) region. On the basis of this database, diatomological maps have been  designed, which are supposed to be of immense help in diagnosis of suspected drowning cases  occurring in this region.
Keywords: diatoms; drowning; water body